The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fpsyg.2022.884512
|View full text |Cite
|
Sign up to set email alerts
|

Reducing and deducing the structures of consciousness through meditation

Abstract: According to many first-person accounts, consciousness comprises a subject-object structure involving a mental action or attitude starting from the “subjective pole” upon an object of experience. In recent years, many paradigms have been developed to manipulate and empirically investigate the object of consciousness. However, well-controlled investigation of subjective aspects of consciousness has been more challenging. One way, subjective aspects of consciousness are proposed to be studied is using meditation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 63 publications
(100 reference statements)
0
5
0
Order By: Relevance
“…Contemplative traditional literature has long suggested that long-term practice of meditation may enable cultivation of unique phenomenological states and prominently one where meditators can cultivate a radical meta-perspective towards mental activity where it appears within consciousness simply as "ongoing phenomena" 4,7,9 . This has been labelled among other things as de-reification, or the process of not reifying mental contents (i.e., not experiencing them as something having a fully objective reality) 4 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contemplative traditional literature has long suggested that long-term practice of meditation may enable cultivation of unique phenomenological states and prominently one where meditators can cultivate a radical meta-perspective towards mental activity where it appears within consciousness simply as "ongoing phenomena" 4,7,9 . This has been labelled among other things as de-reification, or the process of not reifying mental contents (i.e., not experiencing them as something having a fully objective reality) 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Long-term mental training through meditation has been proposed to promote a distinct phenomenological way of consciously experiencing the world, where a meditator can cultivate a meta-perspective on mental contents, as ongoing phenomena constituted within consciousness. This has been labelled decentring 1 , cognitive defusion 2 , mindful attention 3 , dereification 4 , or opacification 5 , and phenomenological 6 or experiential 7 reduction. For example, dereification -i.e., "... the degree to which thoughts, feelings, and perceptions are phenomenally interpreted as mental processes rather than as accurate depictions of reality" -is viewed as a key process associated with mindfulness meditation 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metzinger, instead, conjectures that it could be related to some neurological representational model realized in some brain region with some specific physical properties or neural signatures and correlates that have yet to be discovered Metzinger, 2020 . While Katyal argues that the phenomenology of nondual meditative states suggests that a purely non-representational conscious state–that is, a ‘transcendental’ state beyond conscious experience– may transcend any such neural signatures altogether ( Katyal, 2022 ).…”
Section: From (Lack Of) Evidence To Interpretationmentioning
confidence: 99%
“…We will use 'meditative defabrication' to refer to the Buddhist process specifically, and 'meditative deconstruction' to refer to the AIF interpretation of that process.2 As a consequence we do not discuss the ample literature on the cultivation of the capacity to deconstruct via meditation, under such terms as decentring(Bernstein et al, 2015), cognitive defusion(Fletcher and Hayes, 2005), dereification(Lutz et al, 2015), opacification(Metzinger, 2003) phenomenal reduction(Varela, 1996) and experiential reduction(Katyal, 2022).…”
mentioning
confidence: 99%